Research in entrepreneurship using GEM data: Approach to the state of affairs in gender studies - María de la Cruz Sánchez-Escobedo; Antonio Fernández-Portillo; Juan Carlos Díaz-Casero; Ricardo Hernández Mogollón (European Journal of Management and Business Economics (EJM&BE), 2016)
This paper analyzes the situation and development of research in 'entrepreneurship' from a gender perspective that has used data from the Global Entrepreneurship Monitor (GEM) in the period from 1999 to 2015 in the journals of entrepreneurship included in the Web of Science (WOS). For this purpose, a blibliometric analysis was carried out, which identified the life-cycles of GEM and GEM/gender research, the topics, level of analysis, journals, articles, the most productive authors, the most active countries and institutions and the most used statistical techniques of analysis and data. The main findings of the study show that research on GEM has advanced in recent years; however from a gender perspective by using GEM data, it is in the initial phase, requiring more researchers to be involved, filling the gaps related to topics, macro analysis, or the use of GEM data at both global and regional level.
Keywords: L26; M13; 650; Blibliometrics WOS; Entrepreneurial activity; Entrepreneurship women